Correlation of cholesterol efflux capacity with femoral and carotid plaque volume measured by sonographic 3D plaque volumetry. (2nd May 2022) - Noflatscher, M; Hunjadi, M; Schreinlechner, M; Sommer, P; Lener, D; Mair, F; Theurl, M; Kirchmair, R; Bauer, A; Ritsch, A; Marschang, P
Abstract: Funding Acknowledgements: Type of funding sources: Public grant(s) – National budget only. Main funding source(s): Österreichische Nationalbank Introduction Atherosclerosis is a systemic multifocal disease that can cause the narrowing and occlusion of arteries resulting in cardiovascular disease (CVD). Hypercholesterolemia plays a pivotal role in the pathogenesis of atherosclerotic plaques by the accumulation of cholesterol in the arterial wall. Cholesterol efflux mediated by HDL is capable of transporting cholesterol from the periphery back to the liver in a process called reverse cholesterol transport. Cholesterol efflux capacity (CEC) is inversely correlated with cardiovascular risk and proposed as a surrogate marker for reverse cholesterol transport. In this study, we set out to study a possible association between CEC and peripheral plaque volume. Methods: Since lipid-lowering therapy interferes with CEC, we studied a subset of 176 patients (48.9% females) with a median age of 64 (IQR 57-70) without lipid-lowering medication that had been included in a study of 443 patients with at least one cardiovascular risk factor or established CVD. CETP-mediated cholesterol ester transfer was measured by quantifying the transfer of cholesterol ester from radiolabelled exogenous HDL to apoB-containing lipoproteins. CEC was determined using cAMP treated 3H-cholesterol-labeled J774 cells. Plaque volume in the carotid and the femoral artery was measured using a 3D ultrasound system equipped with semi-automatic software. Results: We found a strong inverse correlation between CEC and high total plaque volume (p = 0.027) in patients without lipid-lowering therapy. On the other hand, there was no correlation between CETP-mediated cholesterol ester transfer (3h) and (16h), LDL- cholesterol, or lipoprotein(a) with total plaque volume. Conclusion: CEC correlates inversely with peripheral atherosclerosis in patients not taking lipid-lowering therapy, further strengthening its role as a cardiovascular biomarker.